Rethinking Development Economics - Stiglitz, Joseph E. (World Bank, 2013)
"Twelve years ago, when I was chief economist of the World Bank, I suggested that the major challenge to development economics was learning the lessons of the previous several decades: a small group of countries, mostly in Asia, but a few in other regions, had had phenomenal success, beyond anything that had been anticipated by economists; while many other countries had experienced slow growth, or even worse, stagnation and decline—inconsistent with the standard models in economics which predicted convergence. The successful countries had followed policies that were markedly different from those of the Washington Consensus, though they shared some elements in common; those policies had not brought high growth, stability, or poverty reduction. Shortly after I left the World Bank, the crisis in Argentina—which had been held up as the poster child of the country that had followed Washington Consensus policies—reinforced the doubts about that strategy.